2016
DOI: 10.1136/jisakos-2015-000013
|View full text |Cite
|
Sign up to set email alerts
|

ACL reconstruction in youth athletes results in an improved rate of return to athletic activity when compared with non-operative treatment: a systematic review of the literature

Abstract: Background Anterior cruciate ligament (ACL) tears are being seen and treated with increasing frequency in youth athletes, with the goal of returning patients to sports activity. This is particularly important for youth athletes, for whom sports provide physical, social and psychological development. Objectives To perform a systematic review of the orthopaedic surgery literature to investigate for any associations between treatment strategy and return to athletic activity after ACL tear in youth athletes under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…Several narrative reviews17 19 85–87 have focused on timing of surgery and additional knee injuries in children and adults. Because a higher proportion of patients with meniscal and cartilage injuries had delayed ACL surgery, authors of narrative reviews have urged early surgery to prevent new meniscal injuries 17 86.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several narrative reviews17 19 85–87 have focused on timing of surgery and additional knee injuries in children and adults. Because a higher proportion of patients with meniscal and cartilage injuries had delayed ACL surgery, authors of narrative reviews have urged early surgery to prevent new meniscal injuries 17 86.…”
Section: Discussionmentioning
confidence: 99%
“…But there is fierce debate about whether ACL reconstruction should be a mandatory part of treatment algorithms that focus on protecting the meniscus 13–16. Some clinicians advocate early ACL surgery to prevent knee instability, and subsequently, new injuries to the menisci and cartilage 17–21. Others advocate early active rehabilitation to improve muscle function and stabilise the knee, only recommending ACL surgery if knee instability persists despite high-quality rehabilitation, or in the presence of repairable meniscal injuries 14 22–24…”
Section: Introductionmentioning
confidence: 99%
“…However, during the 4 years after injury, 33% of the 41 knees required ACL reconstruction for persistent symptoms of instability and 20% sustained new meniscal pathology requiring treatment. Meta-analyses have shown that early stabilization decreases pathological laxity and improves rates of return to activity 4,84 .…”
Section: Nonoperative and Delayed Operative Treatmentmentioning
confidence: 99%
“…Historically, nonoperative management until skeletal maturity followed by traditional ACL reconstruction was a popular treatment strategy. However, the recent understanding of the perils of nonoperative and delayed surgical treatment have supported a trend toward early surgery [4][5][6][7][8][9] . In light of this, surgical techniques and instrumentation have evolved in order to accommodate the unique anatomy of skeletally immature patients.…”
mentioning
confidence: 99%
“…It is considered the standard of care for young active patients who wish to return to sport practice after ACL injury[ 1 ]. Despite the lack of clear evidence of its ability to reduce the onset and progression of knee osteoarthritis (OA), ACL reconstruction is expected to prevent further meniscal and cartilage lesions that could occur in the ACL-deficient knee[ 2 , 3 ]. Usually, ACL reconstruction is performed arthroscopically (occasionally combined with extra-articular plasty/augmentation) using autologous graft such as Gracilis and Semitendinosus tendons (HS), bone-patellar tendon bone (BPTB), and Quadriceps Tendon (QT), or allogenic grafts such as BPTB, Achilles Tendon, and Posterior or Anterior Tibialis tendons.…”
Section: Introductionmentioning
confidence: 99%